Colorectal liver metastases: ADC as an imaging biomarker of tumor behavior and therapeutic response. Issue 137 (April 2021) - Boraschi, Piero; Donati, Francescamaria; Cervelli, Rosa; Pacciardi, Federica; Tarantini, Gaia; Castagna, Maura; Urbani, Lucio; Lencioni, Riccardo
Highlights: Pre-ChT ADC values showed a significant difference between TRG scores, but the distribution was not linear. Post-ChT ADC values and, mostly, ΔADC values, strongly correlated with TRG scores. Each colorectal liver metastasis may have a different response to ChT in the same patient. A significant correlation between the lesion TRG and the evaluation according to RECIST 1.1 criteria was observed. PostADC and ΔADC could be proposed as reliable imaging biomarkers in the response assessment to ChT. Abstract: Purpose: To correlate the ADC values of colorectal liver metastases, evaluated before (preADC) and after (postADC) neoadjuvant chemotherapy (ChT), as well as their difference (ΔADC), with the histological tumor regression grade (TRG) and to determine whether the preADC value can be predictive of the lesion ChT response. Method: Twenty-four patients with colorectal liver metastases, who had undergone 3 T-MRI before and after ChT and were subsequently treated by parenchymal-spearing surgery, were retrospectively included. Diffusion-weighted MRI (DW-MRI) was performed using a spin-echo echo-planar sequence with multiple b values, obtaining an ADC map. Fitted ADC values were calculated for each lesion before and after ChT. The maximum diameter of each lesion in both examinations was recorded. Diameter variations and RECIST1.1 criteria were assessed. All MRI findings were histopathologically correlated to TRG of resected liver metastases. Statistical analysis was performed on a per-lesion basis. Results: A total of 58 colorectal liver metastases were analysed; after ChT, 8 out of 58 lesions disappeared. TRG1, TRG2, TRG3, TRG4 and TRG5 were observed in 6, 12, 12, 13 and 7 lesions, respectively. The preADC values showed a different distribution according to the TRG scores (p = 0.0027), even though the distribution was not linear. The postADC and ΔADC values were significant different based on the TRG system (both p < 0.0001). A significant correlation between the lesion TRG and the evaluation according to RECIST1.1 criteria was observed by a per-lesion analysis (p = 0.0009). Conclusions: PostADC and ΔADC could be proposed as reliable biomarkers to assess tumor treatment response after preoperative ChT in patients with colorectal liver metastases.